Ubiquitous Labour and Differential Dispossession: The Two Faces of Instrumentarian Dystopia - Louis, Shwetha Elsa; Chattopadhyay, Sayan (Surveillance & Society, 2026)
Dystopian fiction routinely employs the trope of surveillance, the various mechanisms for which, while often exemplifying the level of technological advancement the given society has achieved, also demonstrate how scientific innovations invariably become instruments of oppression for the regime in power. This paper, however, deals with surveillance not as a mere apparatus for the incumbent regime but as a mode of production that has coevolved with capitalism called surveillance capitalism. The theoretical lens of the paper is majorly derived from Shoshana Zuboff’s (2019) theorisation of surveillance capitalism. The paper closely reads the dystopian novel Chosen Spirits (2020) by the Indian writer Samit Basu to uncover the ways in which the primary imperative of surveillance in controlling populations conjoins with capital’s drive for exploitation for the production of surplus. The intention of the paper is to demonstrate the dystopian ordering of an instrumentarian society that could give rise to the condition of ubiquitous labour. Contrary to the common assumptions about the universality of dystopian conditions and Zuboff’s (2019) own assumptions regarding the homogenizing experience of surveillance capital, the paper establishes that both surveillance capital and a dystopia built on its structures are experienced differentially depending on one’s social position.